Assessment of Coronary Artery Disease Co-Occurrence in Newly Diagnosed Obstructive Sleep Apnea Patients - Shahzad Anwar , Shadan Sadaf , Mohammad Shameem (South Eastern European Journal of Public Health, 2025)
Background Obstructive Sleep Apnea (OSA) is a prevalent sleep-related breathing disorder with significant cardiovascular implications, particularly its association with Coronary Artery Disease (CAD). The interplay between intermittent hypoxia, systemic inflammation, and endothelial dysfunction links OSA and CAD, increasing the risk of adverse cardiovascular outcomes. Despite this, OSA remains underdiagnosed, especially in patients with CAD, highlighting the need for targeted studies to better understand this association. Aim To assess the co-occurrence of CAD in newly diagnosed OSA patients and to examine the relationship between OSA severity and CAD prevalence. Methods This prospective observational study included 80 participants newly diagnosed with OSA via polysomnography. Participants were categorized into mild, moderate, and severe OSA based on the Apnea-Hypopnea Index (AHI). CAD was evaluated using clinical assessments, electrocardiography, and echocardiography. Statistical analyses, including chi-square tests and regression models, were performed to explore the association between OSA severity and CAD prevalence. Results The preponderance of CAD was 45% among the study participants, increasing significantly with OSA severity: 20% in mild OSA, 43.3% in moderate OSA, and 63.3% in severe OSA (p<0.01p < 0.01p<0.01). Participants with CAD exhibited higher rates of hypertension (78% vs. 45%) and diabetes (56% vs. 32%) compared to those without CAD. Echocardiographic findings revealed elevated NT-proBNP levels (412 ± 110 pg/mL in CAD-positive vs. 182 ± 90 pg/mL in CAD-negative, p<0.01p < 0.01p<0.01) and a higher preponderance of left ventricular hypertrophy in CAD-positive patients (48% vs. 20%, p<0.01p < 0.01p<0.01). Conclusion The study showed that the frequency of CAD and OSA severity were strongly correlated, underscoring the elevated cardiovascular risk in patients with moderate-to-severe OSA. The significance of routine cardiovascular examination in individuals with OSA is highlighted by these findings. Recommendations To reduce cardiovascular risk, integrated care strategies should be used, such as screening for OSA in CAD patients and vice versa. To assess how therapeutic measures, including continuous positive airway pressure (CPAP) therapy, affect cardiovascular outcomes in this population, more study is required.